Penginjilan di Kalangan Generasi Z dan Alpha: Tantangan dan Strategi Kontekstual - Suwito, Herman; Sugiharto, Ayub (Sekolah Tinggi Teologi Berita Hidup, 2025)
This article discusses contextual evangelism among Generation Z and Generation Alpha, who live in an era of digitalization, globalization, and value pluralism. These two generations possess unique characteristics, such as strong attachment to technology, concern for social issues, and a critical tendency toward traditional authority. However, they also face major challenges, including identity crises, technological distractions, and relativism of truth. Using a descriptive qualitative approach, this article examines the theological principles of evangelism rooted in the Great Commission, as well as contextual strategies that can be applied, including digital media, relational approaches, social engagement, and the integration of technology in ministry. The findings indicate that the the message of the Gospel should be shared in a creative way, relevant, and authentic ways in order to be received by Generations Z and Alpha without diminishing its essence. The church and evangelists are called to be creative, relevant, and sensitive to the needs of these generations, while firmly upholding the authority of God’s Word as the unshakable foundation. This article affirms that the church needs to be transformed—not by changing the Gospel, but by adapting its methods of communication—so that it remains effective in fulfilling the Great Commission amidst the changes of the times.